Science Process Skills: Exploring Students' Interpretation Skills Through Communication Skills - Novitasari, Ika; Astuti, Yuni; Safahi, Luthpi; Rakhmawati, Ismi (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
Students must be taught science process skills as a prerequisite for studying the scientific process characteristic of biology. In conveying the practicum outcomes, students employ clear and detailed interpretation and communication skills. This research aims to determine the relationship between communication skills and the development of interpretation skills of the eleventh-grade students of senior high school. The descriptive correlation research method employs test instruments and interviews to collect data. The samples of 54 students were determined using the cluster random sampling technique. The linear regression test was used to analyze the data. According to the findings, communication skills contribute 36% to developing interpretation skills. This study demonstrates that there is a strong relationship between communication skills and interpretation skills. ABSTRAK: Keterampilan proses sains perlu dilatihkan kepada siswa sebagai bekal dalam mempelajari proses ilmiah yang menjadi karakteristik Biologi. Dalam menyampaikan hasil praktikum, siswa menggunakan kemampuan interpretasi dan komunikasi secara jelas dan detail. Penelitian ini bermaksud mempersepsikan hubungan antara keterampilan komunikasi dan pembentukan keterampilan interpretasi siswa SMA kelas XI IPA. Metode penelitian korelasi deskriptif memanfaatkan instrumen tes dan wawancara untuk pengambilan data. Teknik cluster random sampling digunakan untuk penentuan jumlah sampel sebanyak 54 siswa. Data dianalisis dengan uji regresi linier. Berdasarkan hasil yang ditemukan, ada kontribusi keterampilan komunikasi terhadap pembentukan keterampilan interpretasi sebesar 36%. Penelitian ini membuktikan bahwa hubungan antara keterampilan komunikasi dan keterampilan interpretasi berada dalam kategori yang kuat.